Dataset on the synthesis, characterization, and application of MIL-53(Al)@Biomass hybrid for efficient oxytetracycline elimination via adsorption and photocatalysisMendeley Data - Kevin Jhon Fernández-Andrade; Alex Ariel Fernández-Andrade; Luis E. Arteaga-Pérez; Joan Manuel Rodriguez-Diaz (Data in Brief)
Oxytetracycline (OTC) is one of the most used broad-spectrum antibiotics for treating both humans and livestock infections. However, when improperly disposed of, OTC poses a significant risk to water bodies due to its inhibitory effect on water nitrification and its impact on the microbiota. Therefore, various treatments are being investigated to find a sustainable solution for removing oxytetracycline from water. In this sense, adsorption and advanced oxidation processes (AOP) over structured catalytic materials have drawn great attention for their efficiency and selectivity. Important concerns regarding these technical applications are catalyst stability and the proper disposal of adsorbents or catalysts following treatment cycles. Moreover, the elucidation of the underlaying kinetic and thermodynamic mechanisms governing these processes are also of paramount importance for process design and optimization. Accordingly, here we provide a complete dataset on the synthesis and characterization of a novel MOF@Biomass layered hybrid (MIL-53(Al)@RH) for the removal of OTC from water bodies via adsorption and LED-driven photocatalysis. The MIL-53(Al)@RH was synthetized by a microwave-assisted solvothermal method enabling the in-situ hybridization of MIL-53(Al) on rice husk (RH) as a biomass support. The dataset contains information on the physicochemical properties of pristine materials (MIL-53(Al) and rice husk), MIL-53(Al)@RH, and a Carbon-Al obtained via pyrolysis of the saturated MIL-53(Al)@RH (after adsorption). Moreover, data on BATCH adsorption experiments and photocatalytic elimination of oxytetracycline with MIL-53(Al)@RH is also provided. Adsorption data include information on the effect of MIL-53(Al)@RH dosage, solution pH, and kinetics measurements at different initial concentrations of OTC. In addition, data on the photocatalytic activity of MIL-53(Al)@RH is included for different oxidant doses (H2O2), OTC concentrations using a Led-light source.